2006
DOI: 10.1111/j.1525-1438.2006.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter phase II study of the cryptophycin analog LY355703 in patients with platinum-resistant ovarian cancer

Abstract: LY355703 is a synthetic product structurally related to the cryptophycin family isolated from the blue-green algae, which exerts a potent destabilization of microtubules during mitosis. This study was performed to determine the activity of LY355703 in patients with platinum-resistant advanced ovarian cancer and to characterize its toxicity profile. Twenty-six patients were enrolled in this study. Resistant disease was defined as a platinum-free interval of <6 months from primary treatment or rechallenge. LY355… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 15 publications
0
65
0
Order By: Relevance
“…Cryptophycins are naturally occurring compounds isolated from blue-green algae (61). LY355703 is a synthetic cryptophycin derivative, which has shown some activity in platinum-refractory ovarian cancer (61). Although the activity of these compounds in refractory malignancies may be modest, a future role in a variety of settings is possible.…”
Section: Microtubule-destabilizing Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptophycins are naturally occurring compounds isolated from blue-green algae (61). LY355703 is a synthetic cryptophycin derivative, which has shown some activity in platinum-refractory ovarian cancer (61). Although the activity of these compounds in refractory malignancies may be modest, a future role in a variety of settings is possible.…”
Section: Microtubule-destabilizing Agentsmentioning
confidence: 99%
“…Halichondrin B is a large polyether macrolide derived from the marine sponge Halichondria okadaic (60) Eribulin mesylate (E7389) is a synthetic derivative of halichondrin, which is currently in phase II trials in breast, prostate, and NSCLC (60). Cryptophycins are naturally occurring compounds isolated from blue-green algae (61). LY355703 is a synthetic cryptophycin derivative, which has shown some activity in platinum-refractory ovarian cancer (61).…”
Section: Microtubule-destabilizing Agentsmentioning
confidence: 99%
“…57 Cryptophycin-52 (LY355703) reached Phase II clinical trials for non-small cell lung carcinoma (NSCLC) and ovarian cancer previously treated with platinum-based drugs. 58,59 Poor response and unacceptable toxicity was seen in NSCLC patients, while better prognosis was observed in ovarian cancer. This indicated that the dose and schedule of cryptophycin-52 treatment is crucial for activity and in minimizing undesired side effects.…”
Section: Mechanisms Of Action and Direct Cellular Targets Of Biologmentioning
confidence: 99%
“…This indicated that the dose and schedule of cryptophycin-52 treatment is crucial for activity and in minimizing undesired side effects. 58,59 …”
Section: Mechanisms Of Action and Direct Cellular Targets Of Biologmentioning
confidence: 99%
“…They had been a subject of extensive research in past, prompting myriad total synthesis [3,4] and structural modifications [5]. The result of these efforts was the development of cryptophycin-52 (C-52), a synthetic analogue of cryptophycins, which reached phase 2 clinical trials [6,7]. Studies continued to develop new cryptophycin analogues through synthetic or biotechnological methods [8,9] and recently SanofieAventis published two patents on cryptophycin antibody-drug conjugates (ADCs) for treatment of lung cancer [10].…”
Section: Introductionmentioning
confidence: 99%